MORPHOLOGICAL CHARACTERISTICS OF A RED STRAIN OF THE EGYPTIAN AFRICAN CATFISH (Clarias gariepinus BURCHELL 1822) - Bambang Iswanto; Rommy Suprapto; Huria Marnis; Imron Imron (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2016)
Characteristics of the Egyptian African catfish (Clarias gariepinus) strain introduced to Indonesia has not been extensively explored yet, especially the red strain. Previous studies suggested that at the same body length, body weight of the red strain was higher and it was more rotund than that of the normal (black) ones. These differences need to be further investigated to find out which parts of the body mainly contributed to shape the differences. The present study was carried out to explore morphological differences of the red strain of Egyptian African catfish compared to the black strain through morphometric and meristic characterizations. Meristic and morphometric characterizations in the present study were carried out following standard method for morphological characterization of Clarias catfish. The fish samples consisted of each 35 red and black table-sized fish samples resulted from inbred and outbred spawnings. Results of the morphometric and meristic analysis in the present study revealed that the red strain of Egyptian African catfish resulted from inbred spawning of red strain brooders was morphologically different from that of either parental fishes or the black strains. At the same body length, head of the red strain was bigger (wider and longer) than other strains, and its body was stumpy (more rotund and shorter than other strains), deviated from those normal characteristics of the Egyptian African catfish. Its meristic characters were also differed from those of other strains, assigned by reduced dorsal and anal fin rays number.